Paradox of Freedom as Elucidated in Avenged Sevenfold's M.I.A. - Wijaya, Kusuma; Smarandreetha, Falsyawal Galang; Saputro, Dimas Eko; Zaky, Raffi Ahmad; Pasopati, Rommel Utungga (Pioneer: Journal of Language and Literature, 2024)
Humans who have complete freedom tend to feel confused about the choices that exist. They will be confused about what is right and what is not because of the amount of freedom. The song M. I. A. by Avenged Sevenfold tells the story of a soldier who feels confused about his choice when he goes to war. He hopes that what he chooses and does is the right thing, but it is more complex than that. So, how is the Paradox of Freedom reflected in Avenged Sevenfold’s M. I. A.? The analysis involves tensional matters between ‘freedom of’ and ‘freedom to’ in the song through qualitative method. Through the theory of positive and negative freedom by Charles Taylor, people are pushed always to choose positive liberty, but the reality is always negative. It is reflected in this song when goodness never reflects such freedom. Such realization of freedom may also hinder others’ freedom. In conclusion, the paradox of freedom in the song is reflected through the complexities of choices that will emerge one freedom but eliminate another.